2020
DOI: 10.1186/s13287-020-01642-6
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia-preconditioned mesenchymal stem cells prevent renal fibrosis and inflammation in ischemia-reperfusion rats

Abstract: Background Mesenchymal stem cells (MSCs) have been reported to promote the regeneration of injured tissue via their paracrine abilities, which are enhanced by hypoxic preconditioning. In this study, we examined the therapeutic efficacy of hypoxia-preconditioned MSCs on renal fibrosis and inflammation in rats with ischemia-reperfusion injury (IRI). Methods MSCs derived from rats and humans were incubated in 1% O2 conditions (1%O2 MSCs) for 24 h. Aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
61
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 88 publications
(64 citation statements)
references
References 54 publications
1
61
0
2
Order By: Relevance
“…PGE2 has been reported to induce the polarization of immunosuppressive M2 macrophages that produce anti-inflammatory cytokines and inhibit the persistence of inflammation 27 , 28 . In addition, we previously reported that MSCs promoted macrophage differentiation from an M1 pro-inflammatory phenotype to an immunosuppressive M2 phenotype, and that the administration of ex vivo-expanded MSCs suppressed the progression of fibrosis 29 , 30 . Taken together, this suggests that IFN-γ-preconditioned MSCs have a strong immunosuppressive effect and therefore might ameliorate renal fibrosis.…”
Section: Introductionmentioning
confidence: 96%
“…PGE2 has been reported to induce the polarization of immunosuppressive M2 macrophages that produce anti-inflammatory cytokines and inhibit the persistence of inflammation 27 , 28 . In addition, we previously reported that MSCs promoted macrophage differentiation from an M1 pro-inflammatory phenotype to an immunosuppressive M2 phenotype, and that the administration of ex vivo-expanded MSCs suppressed the progression of fibrosis 29 , 30 . Taken together, this suggests that IFN-γ-preconditioned MSCs have a strong immunosuppressive effect and therefore might ameliorate renal fibrosis.…”
Section: Introductionmentioning
confidence: 96%
“…We recently reported that MSCs from EGFP-positive rats persisted for 21 days post-IRI [14]. We further traced MSCs from EGFP-positive rats in IRI kidneys and found they were sparsely detected on day 42 post-IRI (Figure 4A).…”
Section: Localization Of Arterially Delivered Hmscsmentioning
confidence: 79%
“…MSCs mode of action involves a strong paracrine component resulting from active factors secreted in response to the local microenvironment [ 15 , 52 ]. Previous studies have applied HPC to MSCs as a strategy to enhance stem cell survival in vitro, proliferation, and repair capacity [ 53 55 ]. Indeed, restoring MSC paracrine effects through HPC may improve immunomodulatory, angiogenic, antiapoptotic effects, and promote activation of local quiescent stem cells [ 56 ].…”
Section: Discussionmentioning
confidence: 99%